Optimal Carry Trade Strategy Based on Currencies of Energy and Developed Economies - Mikhaylov, Alexey; Sokolinskaya, Natalia; Nyangarika, Anthony (Journal of Reviews on Global Economics, 2018)
Optimal investment strategy depends on the loan in currencies of developed economies (EUR, JPY) and lending in currency of energy economies (RUB, BRL). Since 2014, there has been a shift to euro funding as the currency of financing for carry trade against the backdrop of the European Central Bank (ECB) not changing the volume of incentives to accelerate economic growth. There is some evidence to support the use of euro as a funding currency for carry trade, such as the irrational behavior of the currency during the Greek shock in the middle of 2015. Thus, the impact of yen-based trading strategies on the Japanese stock market is unconventional. It also became evident that the relationship between the dynamics of US dollar and S&P 500 index is extremely uncertain. When risk appetite waned due to the high volatility, the money was back. The ECB’s zero-rate monetary policy has some impact on the global stock market.